2011
DOI: 10.1016/j.ajog.2010.09.025
|View full text |Cite
|
Sign up to set email alerts
|

A molecular signature of an arrest of descent in human parturition

Abstract: Objective-This study was undertaken to identify the molecular basis of an arrest of descent.Study Design-Human myometrium was obtained from women in term labor (TL; n=29) and arrest of descent (AODes, n=21). Gene expression was characterized using Illumina® HumanHT-12 microarrays. A moderated t-test and false discovery rate adjustment were applied for analysis. Confirmatory qRT-PCR and immunoblot was performed in an independent sample set.Results-400 genes were differentially expressed between women with an AO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 297 publications
(112 reference statements)
2
17
0
Order By: Relevance
“…Moreover, native and transfected rat Nmbr exhibit similar binding and signaling characteristics in BALB/3T3 cells [13,]. These results have clearly demonstrated that Nmbr is involved in parturition via a number of signaling pathways in addition to its function in the regulation of the nervous system [33][34][35][36][37].…”
Section: Zhang Et Almentioning
confidence: 91%
“…Moreover, native and transfected rat Nmbr exhibit similar binding and signaling characteristics in BALB/3T3 cells [13,]. These results have clearly demonstrated that Nmbr is involved in parturition via a number of signaling pathways in addition to its function in the regulation of the nervous system [33][34][35][36][37].…”
Section: Zhang Et Almentioning
confidence: 91%
“…Transient decreases of oxygenation, pH, and ATP, all of which if sustained can decrease contractile activity, occur in vivo with each contraction (3)(4)(5). Hypoxia regulates a large number of genes, including those governing metabolism and function in many tissues, and changes in genes associated with hypoxia have been identified as key findings in transcriptomic studies of poorly laboring women (6,7). Chaemsaithong et al and Mittal et al confirmed changes in hypoxia-inducible factor 1a (HIF1a) using RT-PCR, as well as overexpression of cyclooxygenase-2 (COX2) in myometrium and endothelial NOS, which is important for blood vessel dilation.…”
mentioning
confidence: 99%
“…In human pregnancy, HIF1A plays a role in the survival of hematopoietic precursors, embryonic vasculature [146] and trophoblast differentiation [3,44,119] during development [2]. Mittal et al [123] demonstrated a higher expression of HIF1A in the myometrium of patients with an arrest of descent (AOD) than in those with spontaneous term labor. Our findings suggest that during the course of failure to progress in labor (AODIL or AOD), a change in the expression of factors responsible for sensing tissue hypoxia occurs.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with prior reports from our group that focus on arrest of descent. [123]. Mittal et al [123] first characterized the myometrial transcriptome of patients with an arrest of descent; 400 genes were differentially expressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation